Pemetaan distribusi populasi tanaman mangga (Mangifera indica) di Situbondo, Jawa Timur - Elhany, Nurul Avidhah; Fajar, Muhammad Thoifur Ibnu; Rani, Dewi Eka Prawita; Dewi, Yuni Kartika; Hudha, Moh. Nuril; Rahmah, Miftahur (Biogenesis: Jurnal Ilmiah Biologi, 2026)
Situbondo is a district in the province of East Java, Indonesia. Situbondo is a mango production center, in 2019, based on BPS East Java data, produced mango fruit reaching 23,511.70 tons. This research is basic research to determine the potential of mangoes as a food diversification and energy diversification product in Situbondo. Mango mapping in Situbondo Regency is essential as mango is a leading horticultural commodity with high economic value and a strategic role in supporting farmers’ livelihoods. Despite its status as a major mango production center in East Java, spatially explicit information on mango tree distribution, planted area, varieties, and productivity remains limited and unsystematic, hindering effective and sustainable development planning. Moreover, mango cultivation faces increasing threats from land-use change, climate variability affecting flowering and fruiting, pest and disease attacks, and the aging of mango trees, which collectively reduce productivity. Therefore, mango mapping is crucial to provide accurate spatial data for identifying production centers, and conserving local mango varieties, ultimately enhancing sustainable mango management and regional competitiveness. The method used in this research is a survey method with descriptions (explanatory research) of primary data and secondary data. The sample in this study were all mango farmers in Situbondo district. The data obtained was then analyzed using the Simpson's dominance index (D). This index is used to determine the dominance of mango types for each district in Situbondo. The results of mapping and surveying the mango plant population in Situbondo found 3869 trees spread across in 17 district and 28 populations points. The largest population is in Arjasa district with 1872 trees. The mango cultivars recorded in Situbondo district are gadung, manalagi, arum manis, arum merah and garifta.